Matrix Effects of Concomitant Species on the Determination of Nickel by Inductively Coupled Plasma Atomic Emission Spectrometry - Akba, Osman; Baysal, Akin; Merdivan, Melek; Hamamci, Candan; Gumgum, Bahattin (Asian Journal of Chemistry, 2016)
The interference on the determination of nickel by the salts LiCl, NaCl, KCl, CsCl, NH4Cl, Na2SO4, NaNO3, NaC2H3O2 in an inductively coupled plasma-atomic emission spectrometry has been carried out. The salt concentration was in the 100–10000 mg L–1 range. Nickel emission was enhanced at lower matrix concentrations (100 mg L–1). Except cesium, above 100 mg L–1, all studied ions caused a decrease in the signal intensity in the range of 0–15%. The sequence order of the investigated ions for the enhancement and depression was unstable. The sequence order in enhancement was found as Li+ < Na+ < K+ < Cs+ < NH4+ for cation; NO3– < SO42– < Cl– < Oac– for anions and Cs+ < NH4+ < K+ < Li+ < Na+ for cations and Oac– < SO42–, Cl– < NO3– for anions in depression at the studied lines.